2003
DOI: 10.1101/gr.1649303
|View full text |Cite
|
Sign up to set email alerts
|

The Human Transcriptome Map Reveals Extremes in Gene Density, Intron Length, GC Content, and Repeat Pattern for Domains of Highly and Weakly Expressed Genes

Abstract: The chromosomal gene expression profiles established by the Human Transcriptome Map (HTM) revealed a clustering of highly expressed genes in about 30 domains, called ridges. To physically characterize ridges, we constructed a new HTM based on the draft human genome sequence (HTMseq). Expression of 25,003 genes can be analyzed online in a multitude of tissues (http://bioinfo.amc.uva.nl/HTMseq). Ridges are found to be very gene-dense domains with a high GC content, a high SINE repeat density, and a low LI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
291
0
6

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(313 citation statements)
references
References 11 publications
16
291
0
6
Order By: Relevance
“…10e). Intron length in the chicken correlates negatively with recombination (r s ¼ 2 0.774, P , 0.001), G+C content (r s ¼ 2 0.934, P , 0.001) and gene density (r s ¼ 2 0.961, P , 0.001), as has been reported previously for other genomes [120][121][122][123] . The proportion of a chromosome covered by interspersed repeats increases with chromosome length (Fig.…”
Section: Chromosomal Distributions Of Sequence Featuressupporting
confidence: 58%
“…10e). Intron length in the chicken correlates negatively with recombination (r s ¼ 2 0.774, P , 0.001), G+C content (r s ¼ 2 0.934, P , 0.001) and gene density (r s ¼ 2 0.961, P , 0.001), as has been reported previously for other genomes [120][121][122][123] . The proportion of a chromosome covered by interspersed repeats increases with chromosome length (Fig.…”
Section: Chromosomal Distributions Of Sequence Featuressupporting
confidence: 58%
“…This idea is supported by the finding that genes that are similarly expressed are found in clusters (e.g. genes that are co-expressed [5][6][7] and/or broadly expressed [8,9] and/or highly expressed [10,11]). Second, genome proximity might evolve to reduce the recombination rate between specific genes [12,13].…”
Section: Introductionsupporting
confidence: 68%
“…In particular, we examine the hypothesis that transcriptional activity provides a possible mechanistic basis for both clustering phenomena (Hurst and Eyre-Walker 2000;Williams and Hurst 2002;Hardison et al 2003). A priori, a coupling with transcriptional activity is an attractive hypothesis, as genes with comparable expression profile cluster (Caron et al 2001;Lercher et al 2003;Versteeg et al 2003) and expression parameters are related to substitution rates (Duret and Mouchiroud 2000). We show here that transcriptional activity appears not to be an important variable underpinning local similarity of rates of evolution.…”
mentioning
confidence: 99%
“…Prior evidence suggests the possibility of a weak reduction in the synonymous rate of substitution in putatively germline-expressed genes (Duret and Mouchiroud 2000). Given too that it has been shown that highly expressed genes are clustered in the human genome (Caron et al 2001;Versteeg et al 2003), transcriptionally mediated variations in the mutation rate could potentially lead to the observation of local similarity.…”
mentioning
confidence: 99%